Static and Dynamic Characteristics of Steel-Concrete Composite Track Beam of Straddle Monorail with Cluster-Distributed Studs - Shuai Zhou; Peng Yu; Jianguo Nie (Advances in Civil Engineering)
Because the transportation mode of straddle monorail is that the vehicle runs in the state of hugging the track, its track beam is usually a narrow-high cross section. In order to study the static and dynamic characteristics and variation law of prefabricated steel-concrete composite beam of straddle monorail with “cluster-distributed studs” (CDS), a full bridge test model with a scale ratio of 1 : 3 was made. Relevant theoretical analysis, numerical simulation, and model test were carried out, and the data of structural frequency and damping, load-deflection curve, and section height-strain curve were obtained. The results show the following: (1) the equivalent vertical bending stiffness of the composite track beam of straddle monorail is nonlinear. The greater the load, the faster the stiffness decrease, and the greater the difference with the theory of composite beam with “uniformly distributed studs” (UDS). (2) At the same section, the deformation of steel beam and concrete slab is not coordinated along the height direction. The strain value of concrete slab is significantly larger than that of the upper edge of steel beam, so it is difficult to apply the plane-section assumption. (3) Compared with all the measured results of the track beam test, the results of the detailed shell-solid FEM model based on the load-slip curve obtained by push-out test are close to them, and the maximum error is 11.4% difference in stress. (4) Compared with the results obtained by the theoretical formula of the UDS, the results obtained by the theoretical formulas of the CDS based on a “correction coefficient of vertical bending stiffness” proposed in this paper show less deviation comparing to the measured results of the track beam test and are more resilient. When the correction coefficient is 0.9, the maximum error is 23.8% difference in stress. In the design of this kind of structure, the proposed formula can be used for early scheme comparison and later size optimization. Compared with the detailed shell-solid FEM model, the proposed formula significantly reduces the design workload.